Zeros of the lerch transcendent function - Garunkštis, Ramūnas; Grigutis, Andrius (Mathematical Modelling and Analysis, 2012)
We investigate the distribution of zeros of the Lerch transcendent function We find an upper and lower estimates of zeros of the function Φ(q,s,a) in any rectangle s : σ1 < Re s < σ2 ≤ 1.73…, 0 < Im s ≤ T. Further we are interested in a computer calculations concerning the zeros of Φ(q,s,α) in s: Re s > 1, 0 < Im s ≤ 1000.